Macronutrient Status of Soils under Rice Growing Areas of Birbhum District, West Bengal, India - Sunandana Mandal (Journal of the Indian Society of Soil Science, 2022)
The present paper deals with the assessment of the status of macronutrients viz., nitrogen (N), phosphorus(P), potassium (K) and sulphur (S) in relation to soil properties in the selected blocks of Birbhum district,West Bengal. A total of 100 soil samples from 5 blocks (twenty from each five blocks viz., Suri II,Rampurhat II, Md Bazar, Nalhati I and Sainthia) of Birbhum district were collected at a depth of 0-15 cm.Twenty representative villages were chosen from the five selected blocks. Collected soil samples wereanalyzed for pH, electrical conductivity (EC), organic carbon (OC) and macronutrients using standardanalytical methods. The average pH values were found to be 5.24 in Suri II, 6.24 in Rampurhat II, 5.85 inMd Bazar, 7.04 in Nalhati I and 5.30 in Sainthia. Based on the fertility ratings, collected soil samplesvaried between strongly acidic to neutral in soil reaction. The EC values were low and soils were nonsalinein nature. Its value ranged from 0.03 to 0.20 in the selected blocks. Organic carbon content of thesoil samples varied from 0.37 to 0.98%. The average values of OC were found to be 0.61, 0.66, 0.61, 0.71and 0.61, respectively, in Suri II, Rampurhat II, Md Bazar, Nalhati I, Sainthia. The average value ofavailable N were found to be 198.2, 222.0, 229.6, 212.0 and 209.5 kg ha-1 in Suri II, Rampurhat II, MdBazar, Nalhati I and Sainthia, respectively, showing low to medium available N content. The averagevalues of available P were found to be 16.4, 17.9, 15.8, 25.7 and 15.7 kg ha-1 in Suri II, Rampurhat II, MdBazar, Nalhati I and Sainthia, respectively. All the soil samples were found medium in available P except inthe blocks Rampurhat II and Nalhati I. Medium to high available K values were recorded. The average Kcontent of soil samples were found to be 281, 318, 260, 182 and 469 kg ha-1 in Suri II, Rampurhat II, MdBazar, Nalhati I and Sainthia, respectively. All the soil samples were found having low S content. Correlationstudies showed that soil pH correlated significantly and negatively with available N, K and S, whereassignificantly and positively with available P. Significant and positive correlation was recorded between soilOC content and available macronutrients. The EC correlated non-significantly and positively with availableN, P, K and S.